Three Models for Philosophy Teaching in Lithuania - Duoblienė, Lilija (Acta Paedagogica Vilnensia, 2004)
This article deals with the analysis of contemporary way of teaching. Traditional concept of method in our days very often is replaced by others concepts: game, play, those are using to signify the process without awareness results in advance. The main task of this article was to investigate the teaching situation in Lithuania: content of philosophy, the ways of teaching and methodology of textbooks. Some conclusions were formulated: there are three evident tendencies, judging from the organised seminars, publications and textbooks available. The first one is the teaching of philosophical traditions with text interpretation, suggested by J. Baranova and R. Šerpytytė. The second one, by L. Degėsys, is based on critical thinking; and the third one, developed by T.Sodeika, focused on how to be authentic and behave accordingly. The first is backed up by hermeneutic and existential position, the second one – by pragmatic point of view, and Sodeika’s model is based on phenomenological and dialogic view. The problem of teacher in this situation is defined as ambiguity, balancing between existing tradition and teacher’s own position.